Poly(Alkyl Glycidate Carbonate)s as Degradable Pressure‐Sensitive Adhesives. Issue 5 (9th January 2019) - Beharaj, Anjeza; Ekladious, Iriny; Grinstaff, Mark W.
Abstract: Insertion of CO2 into the polyacrylate backbone, forming poly(carbonate) analogues, provides an environmentally friendly and biocompatible alternative. The synthesis of five poly(carbonate) analogues of poly(methyl acrylate), poly(ethyl acrylate), and poly(butyl acrylate) is described. The polymers are prepared using the salen cobalt(III) complex catalyzed copolymerization of CO2 and a derivatized oxirane. All the carbonate analogues possess higher glass‐transition temperatures ( T g =32 to −5 °C) than alkyl acrylates ( T g =10 to −50 °C), however, the carbonate analogues ( T d ≈230 °C) undergo thermal decomposition at lower temperatures than their acrylate counterparts ( T d ≈380 °C). The poly(alkyl carbonates) exhibit compositional‐dependent adhesivity. The poly(carbonate) analogues degrade into glycerol, alcohol, and CO2 in a time‐ and pH‐dependent manner with the rate of degradation accelerated at higher pH conditions, in contrast to poly(acrylate)s. Abstract : Sticking to it under pressure : Degradable poly(alkyl glycidate carbonate)s are synthesized using the salen cobalt(III) complex catalyzed co‐polymerization of CO2 and glycidate. The polymers are new pressure‐sensitive adhesives.